Makna Takut akan Tuhan Menurut Amsal 8:13 (Studi Evaluasi di Jemaat GPdI “Filadelfia” Oepaleo Kupang) - Nelly Nelly; Rodi Imenuel Nome (KAMASEAN: Jurnal Teologi Kristen, 2020)
Abstract: Fear of God are hates evil; hates pride, hates conceit, hates evil conduct, and hates guile-filled mouths. In the fear of God is also a sign of the quality and morality of a person who can be accountable for his life before God and shows a view of life that contains human proper attitudes that are always shown in everyday life because of his good and close relationship with God. The purpose of this study was to describe the meaning of fearing God according to Proverbs 8:13 in the GPdI "Filadelfia" congregation in Oepaleo Kupang. This article is a qualitative research with an evaluation approach, the data is processed and analyzed using descriptive statistics. From the results of the percentage of the five indicators that the researcher included in this study, the average percentage value was in the high criteria, namely 61.81%. In other words, the congregation at GPdI "Filadelfia" Oepaleo Kupang already understands the meaning of fearing God, but it needs to be improved.